High temperature of food and beverage intake increases the risk of oesophageal cancer in Xinjiang, China - Tang, L.; Xu, F.; Zhang, T.; Lei, J.; Binns, Colin; Lee, Andy (Asian Pacific Organization for Cancer Prevention, 2013)
Background: The north-western region of China has a high incidence of oesophageal cancer. This study aimed to investigate whether the intake of food and beverage at high temperature is associated with the risk of oesophageal cancer among adults residing in this remote part of China. Materials and Methods: A case-control study was undertaken in Urumqi and Shihezi, Xinjiang Uyghur Autonomous Region of China, between 2008 and 2009. Participants were 359 incident oesophageal cancer patients and 380 hospital-based controls. Information on temperature of food and beverage intake was obtained by face-to-face interview. Logistic regression analyses were performed to ascertain the association between intake temperature and the risk of oesophageal cancer. Results: The oesophageal cancer patients consumed foods and beverages at higher temperatures than controls, p<0.001. High temperature of tea, water and food intake appeared to increase the risk of oesophageal cancer by more than two-fold, with adjusted odds ratio (95% confidence intervals) of 2.86 (1.73-4.72), 2.82 (1.78-4.47) and 2.26 (1.49-3.45), respectively. Conclusions: Intake of food and beverage at high temperature was positively associated with the incidence of oesophageal cancer in north-western China.